2010
DOI: 10.4049/jimmunol.0902063
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Intrinsic Defects in the Proliferative Response of Antiviral Memory CD8 T Cells in Aged Mice upon Secondary Infection

Abstract: Although previous studies have demonstrated delayed viral clearance and blunted effector T cell responses in aged mice during infection, memory CD8 T cells and especially secondary responses have received less attention. In this study, we show that modest differences in the number of memory CD8 T cells formed in aged versus young animals were associated with altered memory CD8 T cell differentiation. Aged immune mice had increased morbidity and mortality upon secondary viral challenge, suggesting changes in T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
66
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 50 publications
8
66
2
Order By: Relevance
“…Recombinant influenza virus containing the LCMV GP33-41 epitope inserted into the neuraminidase protein stalk region was provided by R. Webby (St. Jude Children’s Research Hospital, Memphis, TN) 5153 . These recombinant influenza virus strains replicate and exhibit pathogenicity similar to that of their non-recombinant counterparts 52 . Viral titers in lungs were determined by qPCR as described 51 .…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant influenza virus containing the LCMV GP33-41 epitope inserted into the neuraminidase protein stalk region was provided by R. Webby (St. Jude Children’s Research Hospital, Memphis, TN) 5153 . These recombinant influenza virus strains replicate and exhibit pathogenicity similar to that of their non-recombinant counterparts 52 . Viral titers in lungs were determined by qPCR as described 51 .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, peak GZMA mRNA expression was reduced in aged ferrets (Figure 3 ix). Together, these findings suggest a potential age-related decrease in type 1 T-cell responses specific to heterologous 2° challenge which may have contributed to disease (Bender and Small, 1993; Decman et al, 2010). …”
Section: Resultsmentioning
confidence: 87%
“…Heterosubtypic influenza A immune memory is severely impaired in aged animals (Bender and Small, 1993; Decman et al, 2010), although the elderly's sensitivity to monosubtypic antigenic change is unclear. To address this question, we investigated clinical morbidity, viral dynamics, and subsequent immune responses to sequential influenza A H1N1 infection for the first time in an aged ferret model.…”
Section: Introductionmentioning
confidence: 99%
“…Normal aging is associated with increased health risk, as vaccine efficacy wanes and susceptibility to, and severity of, a variety of infections and malignancies is enhanced (1,2). Whereas aging compromises a number of arms of the immune system (3), studies in mice and humans have demonstrated deficits that are intrinsic to naïve CTL populations (4)(5)(6). Thus, a complete understanding of both age-related CTL deficiencies and the underlying mechanisms is critical.…”
mentioning
confidence: 99%